Effect of Weave Parameters on the Tear Strength of Woven Fabrics. Issue 9 (1st September 2020) - Thanikai Vimal, J.; Prakash, C.; Jebastin Rajwin, A.
ABSTRACT: The fabric tear strength is an important parameter in textile material, ever since it is close to relate to the service of the fabric. Tear strength of the fabrics depends on the flexibility of the yarn in fabric structure. In this research, the tear strength of 11 cotton woven fabrics is analyzed based on the weave parameters such as crossing over firmness factor (CFF), Floating Yarn Factor (FYF), Fabric Firmness Factor (FFF) and weave factor (P1).